Development of Glyceryl Monostearate Based Ciprofloxacin Hydrochloride Sustained Release Matrix Tablet: an In vitro Study - Laila, Susmita; Haque, Tasnuva; Taluker, Md Mesbah Uddin; Ahmed, Ishtiaq; Islam, Muhammad Rashedul; Rahman, Md Habibur (Dhaka University Journal of Pharmaceutical Sciences, 2010)
In this present study an attempt has been made to evaluate glyceryl monostearate (GMS) as a rate retarding material to sustain the release ciprofloxacin hydrochloride from the matrix tablet. The solubility of ciprofloxacin hydrochloride was studied. The physical parameters of the prepared tablets were also evaluated. Release kinetics of ciprofloxacin hydrochloride from this sustained release matrix was studied in 0.1 N HCl using United States Pharmacopoeia type-II dissolution apparatus (paddle method). The effect of polymer load, drug load, hydroxylpropylmethylcellulose to compensate glyceryl monostearate (GMS) and different release modifiers were examined. It was observed that the release rate of drug was retarded with the increasing concentration of GMS. The release data were treated in different fashion to identify the release mechanism and it was revealed with few exception that, when GMS is used as single polymer, release of active drug from the prepared matrix tablet appeared to follow the first order kinetics and showed the tendency to follow Korsmeyer model when HPMC 15 cps was used along with GMS. Using release enhancers the release pattern were fitted to first order kinetics. From the f2 values it can be concluded that the release pattern of P-2, D-1, H-2 and H-3 are similar to P-1, whereas the formula of P-1, D-2 and H-1 were same. MDT values were found to be increased with the increasing amount of polymer (GMS). Key words: Glyceryl monostearate; ciprofloxacin HCl; sustained release matrix; dissolution studies. DOI: 10.3329/dujps.v8i1.5340 Dhaka Univ. J. Pharm. Sci. 8(1): 81-88, 2009 (June)